PERBUATAN MELAWAN HUKUM DALAM SENGKETA EKONOMI SYARIAH DAN ALTERNATIF PENYELESAIANNYA MELALUI MEDIASI DAN ARBITRASE DI INDONESIA - Alamudi, Ichwan Ahnaz (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2024)
This article is motivated by the phenomenon of the development of Islamic economics that occurs will be very likely to cause disputes over matters related to Islamic economics. Dispute resolution in Indonesia can be implemented in two ways, namely litigation and non-litigation, one of the causes of disputes is the existence of aspects or elements of unlawful acts. This article uses a descriptive qualitative approach that is more specific to the data library or library research. In this paper the authors produce that unlawful acts in the context of Islamic economics can be seen in the form objeknya ghasab, itlaf, Al-Ta'asuf Fi isti'm